2018
DOI: 10.1590/s1679-45082018ao4092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics associated with referral of hospitalized elderly to palliative care

Abstract: ObjectiveTo investigate clinical and laboratory characteristics associated with referral of acutely ill older adults to exclusive palliative care.MethodsA retrospective cohort study based on 572 admissions of acutely ill patients aged 60 years or over to a university hospital located in São Paulo, Brazil, from 2009 to 2013. The primary outcome was the clinical indication for exclusive palliative care. Comprehensive geriatric assessments were used to measure target predictors, such as sociodemographic, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
3
0
10
Order By: Relevance
“…In a pre-pandemic Brazilian cohort of 572 medical admissions of adults over the age of 60 years carried out in hospital 2, Arcanjo et al found that male sex, cancer, advanced dementia, and low albumin levels were independently associated with palliative care referral( 13 ). Conversely, we have examined patients aged 50 years or older, all admitted for COVID-19, and have identified additional predictors of palliative care including frailty, which has been recently associated with worse prognosis of COVID-19 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pre-pandemic Brazilian cohort of 572 medical admissions of adults over the age of 60 years carried out in hospital 2, Arcanjo et al found that male sex, cancer, advanced dementia, and low albumin levels were independently associated with palliative care referral( 13 ). Conversely, we have examined patients aged 50 years or older, all admitted for COVID-19, and have identified additional predictors of palliative care including frailty, which has been recently associated with worse prognosis of COVID-19 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we opted to capture clinical information that would most likely identify patients in palliative care. Previous studies have used similar strategies in the past( 13 , 21 ). Second, the two participating centers are traditional public teaching hospitals in Sao Paulo with established palliative care groups.…”
Section: Discussionmentioning
confidence: 99%
“…Embora um em cada quatro idosos gravemente enfermos internados em alas geriátricas seja encaminhado para cuidados paliativos, não há um consenso a melhor forma de se avaliar e comunicar o prognóstico em populações geriátricas. O estabelecimento de melhores diretrizes clínicas pode contribuir para a identificação precoce de pacientes hospitalizados, que poderiam se beneficiar de cuidados paliativos, além de fornecer informações relevantes a pacientes e cuidadores envolvidos no processo de tomada de decisão (Arcanjo, et al, 2018).…”
Section: Resultsunclassified
“…As doenças crônicas mais frequentes em serviços de cuidados paliativos são demência avançada, câncer e doenças cardíacas e circulatórias. 4,5 Apesar de existirem estudos que testam os escores prognósticos em ambientes não hospitalares e em pacientes não exclusivamente oncológicos, 6,7 eles normalmente focam em pacientes oncológicos e em ambiente hospitalar. 8,9 Grande parte desses trabalhos é realizada em outros países, gerando a necessidade de estudos nacionais com população heterogênea e em ambientes diferentes, como o Serviço de Atenção Domiciliar (SAD).…”
Section: Introductionunclassified